Cascaded Graphene Frequency Selective Surface Integrated Tunable Broadband Terahertz Metamaterial Absorber - Rishi Mishra; Arpit Sahu; Ravi Panwar (IEEE Photonics Journal)
The quest of novel materials and structures to design an efficient absorber for realizing wave trapping and absorption at terahertz (THz) frequencies is an open topic. But the design of a thin, wideband, and tunable THz absorber is still an arduous job. Hence, in this paper, a hybrid THz metamaterial absorber integrated with a cascaded graphene frequency selective surface (FSS), with ultra-high absorbance over a wide frequency range is designed using an analytical equivalent circuit model. Such an approach provides a feasible way to optimize the device by interrelating the effective electromagnetic and circuit parameters with the unit cell dimensions of FSS. A systematic study and critical analysis over a wide range of device parameters including graphene chemical potential and FSS design variables is demonstrated. A peak dip in reflection coefficient of −30.27 dB is observed at 2.94 THz for an optimal device with a chemical potential (μc) of 0.38 eV (μc1), and 0.25 eV (μc2) in the range of 0.1–4.0 THz. The cascaded FSS configuration results in the unique anti-reflection-based absorption phenomena, which is responsible for the achievement of –10 dB absorption bandwidth of 2.34 THz (0.85–3.19 THz). In addition, the frequency-dependent effective permittivity, permeability, and impedance is extracted using reflection data, in order to understand the device physics. Such ultra-thin and broadband absorbing device architecture may confer potential application perspectives in THz sensing, imaging, and detection.